Vaccination with Leishmania infantum acidic ribosomal P0 but not with nucleosomal histones proteins controls Leishmania infantum infection in hamsters. - Lais Pereira; Melissa Abbehusen; Clarissa Teixeira; Jurema Cunha; Ivan P Nascimento; Ivan P Nascimento; Kyioshi Fukutani; Washington dos-Santos; Aldina Barral; Camila Indiani de Oliveira; Manoel Barral-Netto; Manoel Soto; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND: Several intracellular Leishmania antigens have been identified in order to find a potential vaccine capable of conferring long lasting protection against Leishmania infection. Histones and Acid Ribosomal proteins are already known to induce an effective immune response and have successfully been tested in the cutaneous leishmaniasis mouse model. Here, we investigate the protective ability of L. infantum nucleosomal histones (HIS) and ribosomal acidic protein P0 (LiP0) against L. infantum infection in the hamster model of visceral leishmaniasis using two different strategies: homologous (plasmid DNA only) or heterologous immunization (plasmid DNA plus recombinant protein and adjuvant). METHODOLOGY/PRINCIPAL FINDINGS: Immunization with both antigens using the heterologous strategy presented a high antibody production level while the homologous strategy immunized group showed predominantly a cellular immune response with parasite load reduction. The pcDNA-LiP0 immunized group showed increased expression ratio of IFN-γ/IL-10 and IFN-γ/TGF-β in the lymph nodes before challenge. Two months after infection hamsters immunized with the empty plasmid presented a pro-inflammatory immune response in the early stages of infection with increased expression ratio of IFN-γ/IL-10 and IFN-γ/TGF-β, whereas hamsters immunized with pcDNA-HIS presented an increase only in the ratio IFN-γ/ TGF-β. On the other hand, hamsters immunized with LiP0 did not present any increase in the IFN-γ/TGF-β and IFN-γ/IL-10 ratio independently of the immunization strategy used. Conversely, five months after infection, hamsters immunized with HIS maintained a pro-inflammatory immune response (ratio IFN-γ/ IL-10) while pcDNA-LiP0 immunized hamsters continued showing a balanced cytokine profile of pro and anti-inflammatory cytokines. Moreover we observed a significant reduction in parasite load in the spleen, liver and lymph node in this group compared with controls. CONCLUSIONS/SIGNIFICANCE: Our results suggest that vaccination with L. infantum LiP0 antigen administered in a DNA formulation could be considered a potential component in a vaccine formulation against visceral leishmaniasis.